Reduced Susceptibility to Neuraminidase Inhibitors in Influenza B Isolate, Canada - Yacine Abed; Clément Fage; Patrick Lagüe; Julie Carbonneau; Jesse Papenburg; Donald C. Vinh; Guy Boivin (Emerging Infectious Diseases, 2019)
We identified an influenza B isolate harboring a Gly407Ser neuraminidase substitution in an immunocompromised patient in Canada before antiviral therapy. This mutation mediated reduced susceptibility to oseltamivir, zanamivir, and peramivir, most likely by preventing interaction with the catalytic Arg374 residue. The potential emergence of such variants emphasizes the need for new antivirals.